Taking stock: protocol for evaluating a family planning supply chain intervention in Senegal. Issue 1 (December 2016) - Cavallaro, Francesca; Duclos, Diane; Baggaley, Rebecca; Penn-Kekana, Loveday; Goodman, Catherine; Vahanian, Alice; Santos, Andreia; Bradley, John; Paintain, Lucy; Gallien, Jérémie; Gasparrini, Antonio; Hasselback, Leah; et al.
Abstract Background In Senegal, only 12 % of women of reproductive age in union (WRAU) were using contraceptives and another 29 % had an unmet need for contraceptives in 2010–11. One potential barrier to accessing contraceptives is the lack of stock availability in health facilities where women seek them. Multiple supply chain interventions have been piloted in low- and middle-income countries with the aim of improving contraceptive availability in health facilities. However, there is limited evidence on the effect of these interventions on contraceptive availability in facilities, and in turn on family planning use in the population. This evaluation protocol pertains to a supply chain intervention using performance-based contracting for contraceptive distribution that was introduced throughout Senegal between 2012 and 2015. Methods This multi-disciplinary research project will include quantitative, qualitative and economic evaluations. Trained researchers in the different disciplines will implement the studies separately but alongside each other, sharing findings throughout the project to inform each other's data collection. A non-randomised study with stepped-wedge design will be used to estimate the effect of the intervention on contraceptive stock availability in health facilities, and on the modern contraceptive prevalence rate among women in Senegal, compared to the current pull-based distribution model used for other commodities. Secondary data from annual Service Provision Assessments and Demographic and Health Surveys will be used for this study. Data on stock availability and monthly family planning consultations over a 4-year period will be collected from 200 health facilities in five regions to perform time series analyses. A process evaluation will be conducted to understand the extent to which the intervention was implemented as originally designed, the acceptability of third-party logisticians within the health system and potential unintended consequences. These will be assessed using monthly indicator data from the implementer and multiple ethnographic methods, including in-depth interviews with key informants and stakeholders at all levels of the distribution system, observations of third-party logisticians and clinic diaries. An economic evaluation will estimate the cost of the intervention, as well as its cost-effectiveness compared to the current supply chain model. Discussion Given the very limited evidence base, there is an important need for a comprehensive standardised approach to evaluating supply chain management, and distribution specifically. This evaluation will help address this evidence gap by providing rigorous evidence on whether private performance-based contracting for distribution of contraceptives can contribute to improving access to family planning in low- and middle-income countries.